2015
DOI: 10.1103/physrevlett.114.133201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Singlet Scattering Channels in Long-Range Rydberg Molecules

Abstract: We observe the formation of long-range Cs2 Rydberg molecules consisting of a Rydberg and a ground-state atom by photoassociation spectroscopy in an ultracold Cs gas near 6s 1/2 (F =3,4)→np 3/2 resonances (n=26-34). The spectra reveal two types of molecular states recently predicted by D. A. Anderson, S. A. Miller, and G. Raithel [Phys. Rev. A 90, 062518 (2014)]: states bound purely by triplet s-wave scattering with binding energies ranging from 400 MHz at n=26 to 80 MHz at n=34, and states bound by mixed singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
142
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(164 citation statements)
references
References 29 publications
10
142
4
4
Order By: Relevance
“…The original observations were of dimers involving spherically symmetric S Rydberg states [2], but now measurements have been extended to anisotropic P [5,6] and D [7,8] Rydberg states and to molecules comprising one Rydberg atom and as many as four ground state atoms [9]. Excitation of Rb(nD) [9] and Cs(nP ) [6] Rydberg molecules has revealed considerable spectral complexity due to the Rydberg electron spin-orbit and ground-state hyperfine interactions, which results in mixing of singlet and triplet electronic symmetries. For bosonic alkaline-earth metal atoms, such as 84 Sr studied here, both these interactions are absent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The original observations were of dimers involving spherically symmetric S Rydberg states [2], but now measurements have been extended to anisotropic P [5,6] and D [7,8] Rydberg states and to molecules comprising one Rydberg atom and as many as four ground state atoms [9]. Excitation of Rb(nD) [9] and Cs(nP ) [6] Rydberg molecules has revealed considerable spectral complexity due to the Rydberg electron spin-orbit and ground-state hyperfine interactions, which results in mixing of singlet and triplet electronic symmetries. For bosonic alkaline-earth metal atoms, such as 84 Sr studied here, both these interactions are absent.…”
mentioning
confidence: 99%
“…Gaps in laser coverage prevented measurement of spectra for n = 31 and n = 32. The binding energies of deeply bound states follow the approximate 1/(n − δ) 6 scaling initially seen in Rb [9], which reflects the scaling of the Rydberg-electron probability density |ψ ns (R)| 2 at the location of the groundstate Sr atom. Deviations from the scaling are evident for weakly bound states and are clearly seen in high-quality spectra for n = 30.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial experiments focused on creation of dimer molecules comprising a ground-state rubidium atom bound to a spherically-symmetric Rb(ns) Rydberg atom [2]. Measurements have since been extended to include other Rydberg species, anisotropic P and D Rydberg states and, using Cs(ns) Rydberg atoms, to the creation of so-called trilobite states with very large permanent electric dipole moments [3][4][5][6][7][8][9][10][11][12]. Detailed spectroscopic studies have revealed the formation of molecules comprising one Rydberg atom and up to four bound ground-state atoms [13].…”
Section: Introductionmentioning
confidence: 99%
“…These ultralong-range Rydberg molecules were first experimentally observed for Rb atoms in a swave Rydberg state [14], and current experiments focus on exploring these Rydberg molecules formed by higher angular momentum Rydberg states [15, 17? -20], and by other atomic species such as Cs [18,19] and Sr [21,22]. In a mixture of ultracold atoms and ultracold molecules, Rydberg atoms could be created by standard two-photon excitation schemes.…”
Section: Introductionmentioning
confidence: 99%